Aplicação da fluidodinâmica computacional na avaliação da hidrodinâmica de estágio em colunas de destilação - Justi, Gabriel Henrique (Universidade Federal de São Carlos, 2012)
The development of the design of chemical processes has received increasing improvement, incorporating sophisticated mathematical models, which allowed better simulation of its real behavior. The distillation column is one of the most widely used separation equipment in the industry and therefore, its perfect working and optimization are economically crucial factors. Thus, the study of the hydrodynamic in distillation column sieve trays has increased over the years with the purpose to optimize the flow patterns, which is of great importance on the mass and energy transfer efficient. Due to the development of powerful computers, advances in numerical methods and improvement in models of multiphase flows, the investigation of complex flow problems is possible. One way to investigate these problems is to use Computational Fluid Dynamics. Thus, in this work we used commercial package CFD software to predict the hydrodynamics in a sieve tray, with the main objective to evaluate the velocity fields and compare them with the experimental work of Solari and Bell (1986). We proposed a two-fluid model with Eulerian-Eulerian framework, three-dimensional (3D), steady-state and the standard k-ε turbulence model for air/water system at 1 atm. The continuity and momentum conservation equations were used to describe the gas and liquid phases. The simulated sieve tray geometry was based on experimental work of Solari e Bell (1986). The simulation domain included the downcomer region. New sieve tray geometry design was proposed to evaluate the hydrodynamics. The results show the velocity profiles, volume fractions and liquid recirculation zones on the sieve tray for several combination of liquid and gas flow rates. The simulation indicated the presence of recirculation and stagnation zones, and it reproduced satisfactorily the results of Solari e Bell (1986) and the new geometry design reduced the liquid recirculation zones on tray. The proposed methodology in this work proved to be appropriate and the Computational Fluid Dynamics (CFD) techniques presented to be an important tool in the design and optimization of sieve trays.
Keywords: Fluidodinâmica computacional; Prato perfurado; Hidrodinâmica; Destilação; Engenharia química; Simulação computacional; Computation Fluid Dynamics; Sieve tray; Hydrodynamic; Distillation; ENGENHARIAS::ENGENHARIA QUIMICA